2010
DOI: 10.1007/s11096-010-9429-2
|View full text |Cite
|
Sign up to set email alerts
|

Generic and therapeutic substitutions: are they always ethical in their own terms?

Abstract: Cost containment-driven drug substitution, whether generic or therapeutic, is defined as switching to another drug because it is cheaper. So far, such substitutions have drawn their public legitimacy from the general belief that they would not compromise the clinical interests of patients and certainly not violate their right to decline them if they did. This article does not enter the debate on whether or not such substitutions must give exclusive priority to the patient's interests and choices in order to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…But some authors and general practitioners are now questioning the quality of some cheaper medicines [11][12][13][14][15][16][17][18][19]. Without consulting patients, and thus obtaining their consent to treatment, many healthcare providers including the British NHS have been promoting drug substitution in an attempt to contain their costs [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But some authors and general practitioners are now questioning the quality of some cheaper medicines [11][12][13][14][15][16][17][18][19]. Without consulting patients, and thus obtaining their consent to treatment, many healthcare providers including the British NHS have been promoting drug substitution in an attempt to contain their costs [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Random switching among generic versions of the same drug is also not suggested [17,18]. A study reported that indiscriminate switching among generic versions of branded drug could potentially result in 40-60% differences in rate or extent of absorption [34].…”
Section: Renal Transplant Patients' Views On Generic Substitution In mentioning
confidence: 99%
“…In their commentary on the ethical aspects of generic and therapeutic substitution, AlAmeri et al [1] argued that the health economic rationale for promoting substitution, i.e. the creation of cost savings to the health care system, may be harmful to patients and, thus, that substitution is unethical.…”
Section: To the Editormentioning
confidence: 99%
“…In his response to our paper [1], Simoens complains that we ''focus on the individual patient's perspective to the detriment of the societal perspective''. He goes further to explicate what health economics, his field, perceives to be the 'societal perspective'.…”
Section: To the Editormentioning
confidence: 99%